Do Interest Rate Liberalization and Fintech Mix? Impact on Shadow Deposits in China. Issue 1 (16th February 2020) - Chan, Stephanie; Ji, Yang
Abstract: In this paper we attempt to characterize the stability of shadow deposits in China with interest rate liberalization and fintech developments. We emphasize that shadow banks provide higher but riskier returns and such characteristics affect the stability of shadow deposits. In our setting, the stability of shadow deposits is influenced by two offsetting effects, namely: the patience effect, which makes investors more willing to wait because of the potentially higher returns; and the uncertainty effect, which makes investors more likely to withdraw as a result of higher risk. Under liberalized interest rates, the patience effect will erode and the uncertainty effect will be heightened because the post‐liberalization higher return of traditional banks undermines the importance of the extra return of shadow deposits to depositors, while preserving the importance of the risk aspect. Fintech development is modeled as a reduction in the withdrawal cost that facilitates runs. This affects the stability of shadow deposits because of their wider fintech reliance. Regulators should be cautious in pushing interest rate liberalization and fintech application alongside building a safety net for shadow banking.